Enhancement efficiency of organic Rankine cycle by using sorption system. (25th July 2017) - Chaiyat, Nattaporn; Wakaiyang, Yiayang; Inthavideth, Xangpheuak
Highlights: Use of sorption cooling to improve the ORC cycle efficiency by reducing the ORC condenser temperature. Energy, exergy and economic impacts of the integrating ORC-sorption units are considered. Performance curves of the ORC and sorption systems are developed from testing results. The optimal ORC-sorption unit is evaluated by projection process. Abstract: This paper focuses a method to enhance an organic Rankine cycle (ORC) efficiency by using the sorption systems (absorption and adsorption) for reducing the ORC condenser temperature. Energy efficiency, exergy efficiency and levelized electricity cost (LEC) are used to evaluate the optimal combined unit. Testing data from a 25 kWe R-245fa ORC prototype, a 1 TR water-LiBr absorption chiller and a 1 TR water-silica gel adsorption refrigeration are tested and analyzed performance curve of each technology to predict thermal performance of the ORC-sorption units at various operating conditions. Projection of the integrating unit of the ORC and sorption systems represent the better energy and exergy efficiencies, when the ORC condenser temperature is decreased. The ORC-absorption efficiencies in terms of energy and exergy increase 7.22%, while the ORC-adsorption system improve 12.46% compared with the normal ORC efficiencies. In economic impact, the LEC of the normal ORC unit is 0.1145 USD/kW h, which is higher than the ORC-absorption unit and the ORC-adsorption unit of 0.1088 USD/kW h and 0.1043 USD/kW h, respectively, at chilled water temperature output the absorption system at 7 °C. Thus, it could be concluded that the ORC-adsorption system is the optimal technique to enhance the ORC electricity generation process in terms of energy efficiency, exergy efficiency and electricity cost.